Introduction to quantum mechanics with applications to chemistry - Pauling, Linus, 1901-1994 (Dover Publications, 1985)
This widely adopted undergraduate-level text applies quantum mechanics to a broad range of chemical and physical problems, covering such subjects as wave functions for the hydrogen atom, perturbation theory, the Pauli exclusion principle, and the structure of simple and complex molecules. Numerous tables and figures.
Reprint. Originally published: New York ; London : McGraw-Hill, 1935.
Keywords: Quantum theory.; Wave mechanics.; Chemistry, Physical and theoretical.; elektronické knihy; electronic books